Factors Associated with the Survival Outcome of Hepatocellular Carcinoma Patients on Supportive Care in a Tertiary Hospital in South-West Nigeria - Adekanle, Olusegun; Ijarotimi, Oluwasegun; Komolafe, Akinwumu Oluwole; Olowookere, Samuel Anu; Famurewa, Comfort Olusola; Ndububa, Dennis A. (European Scientific Journal, ESJ, 2019)
Background: Hepatocellular carcinoma (HCC) is a primary liver cancer. This study assessed the factors associated with the survival outcome of HCC on supportive care. Methods: This was a prospective cohort study carried out from January 2010 to June 2016 on cases of HCC recruited into a cancer data registry. Clinical, laboratory and survival outcomes were obtained. Data obtained were analyzed using descriptive and inferential statistics. Results: A total of 149 cases were analyzed: 120 (80.5%) males and 29 (19.5%) females. Age range was 18-87years, with mean (SD) being 45.0 (14.3) years. Identifiable aetiological factors were hepatitis B and C viruses, alcohol and herbal preparations in 94% while no risk factor was identified in 6%. Some risks co-occurred in multiples in 71.2% of cases. The overall median survival was 20 days, and general survival was 59.1% at two weeks, 33.6 % at one month, and only 7.3% surviving beyond thirty one days to two years. The survival of cases, according to the Child-Pugh (CTP) class, was CTP A: 36 days (ranged 4 to 730 days), CTP class B: 22 days (ranged 1 to 210 days) and CTP class C: 14 days (ranged 2 to 660 days). Higher proportion of young cases was HBsAg positive. Factors significantly associated with survival outcome included older age, female sex, abdominal pain, jaundice, elevated creatinine, bilirubin, AST, ALT, white cell count and hyponatreamia. Conclusion: Overall survival outcome among cases of HCC was poor. It is necessary to prevent HBV, reduce alcohol use, detect and treat HCC early.